A Novel Through‐the‐Wall Imaging Algorithm Combined with Phase Shift Migration and NUFFT. Issue 5 (1st September 2017) - Zhang, Peng; Fei, Peng; Wen, Xin; Nian, Feng
Abstract : This paper proposes a novel Through wall imaging (TWI) algorithm combined with phase compensation and Nonuniform fast Fourier transform (NUFFT). The wall effect is cancelled with phase compensation, which is implemented by multiplying the conjugated wall transmissivity with the received echoes. The NUFFT technique is implemented to calculate the imaging results. The proposed method has two merits: The phase compensation avoids a time‐consuming calculation of the incidences angles; the image is reconstructed more accurately and efficiently than the conventional Interpolation‐fast Fourier transform (IPFFT) method. The new method is implemented on 2D synthetic‐generated data and experimental data. The results demonstrate that our method generates high quality focused images and achieves target geometrical identification within a very short time.